Absorption of Water Vapor by Bambus[6]uril and a Density Functional Theory Study of Its Aqua Complexes; Molecules; Vol. 28, iss. 23 - Turebayeva P. Pana; Guslyakov A. N. Aleksey Nikolaevich; Novikova S. A. Svetlana Alekseevna; Khlebnikov A. I. Andrey Ivanovich; Befus E. A.; Meshcheryakov E. P. Evgeny Pavlovich; Bakibaev A. A. Abdigali Abdimanapovich; Kusepova L. A. Lyazat Amanzholovna; Kasenova N. B. Nazira Bazarbaevna; Sharipova S. A. Sarzhan Aubakirovna; Yerkassov R. Sh. Rakhmetulla Sharapidenovich (2023, 2023)
Title screen